(untitled) (Zaporizhzhia Historical Review, 2021)
The process of the transformations of native Pentecostal religion centers are under consideration. The author aims to prove that the integration tendencies in environment of Pentecostal caused the centralization in their structure and caused the establishment in native religion range.